JOURNAL OF GOVERNMENT & POLITICS : Politics and Religious Freedom in Indonesia : The Case of West Sumatra and North Sulawesi - Delmus Puneri Salim , Srifani Simbuka (FISIPOL UMY, 2016)
Since the introduction of decentralization, regions in Indonedsia have promoted regional philosophies that guide their development.